CHILDHOOD MENTAL HEALTH: AN ECOLOGICAL ANALYSIS OF THE EFFECTS OF NEIGHBORHOOD CHARACTERISTICS. Issue 8 (November 2016) - Kemp, Gail N.; Langer, David A.; Tompson, Martha C.
Abstract : Research on childhood mental illness traditionally examines risk factors most proximal to the child. However, current trends reflect growing interest in how broader contextual factors contribute to psychopathology risk. In this study, we examined neighborhood‐level indicators as potential sources of chronic strain in a sample of 156 mother–child dyads; children were 8 to 12 years old. For most neighborhood indicators, data were collected at the level of census tracts using publicly available data sets. We hypothesized that these indicators would be both associated with greater overall mental health symptoms and specifically predictive of childhood symptoms of depression. We also examined potential mediators (maternal functioning and family cohesion) and moderators (maternal depression). Neighborhood indicators correlated with parents' ratings of children's overall mental health problems, but did not correlate with children's self‐report of depression symptoms. Maternal functioning mediated neighborhood effects on children's overall mental health problems. Implications and directions for future research are presented.